Pertimbangan Hakim dalam Menangani Tuntutan Pengembalian Uang Belanja Pada Pengadilan Agama - Nur Atika; Abdul Rahman Sakka; Fransiska Gobe (Al-Azhar Islamic Law Review, 2021)
One of the problems faced by a judge when deciding on a divorce case is the case of refunding spending money. Regarding spending money, it becomes a new problem and legal case when a wife files for divorce (khulu) to her husband in court (especially if the wife has not been interfered with), then her husband demands a refund of the spending money.This study uses a type of field research (field research), namely research in which data collection is carried out in the field, in this study is a legal sociology approach. The sociology of law approach is used to evaluate and examine the influence of law on social behavior, the beliefs held by people in the social world in relation to customary justice, social organizations, social developments and legal institutions, social conditions that give rise to law.The results of the study show that (1) the basis for the judge's consideration in deciding cases of demands for a refund of expenditures to settle cases of demands for a refund of expenditures there are 3 methods, namely: The method of juridical considerations bases its decision on the provisions of the legislation formally in the form of evidence. namely, documentary evidence (written), witness evidence, suspicion (allegations), confessions and oaths, the Sociological Method. And Philosophical Methods. (2) The judge in handling the demands for the refund of spending money is based on Islamic law, by conducting ijtihad or legal discovery by tying up or analogizing spending money with a dowry because of Qobla Dukhul. Because no legal basis is found in the Qur'an and al-Hadith.